2006
DOI: 10.1073/pnas.0604844103
|View full text |Cite
|
Sign up to set email alerts
|

Two isoforms of tissue transglutaminase mediate opposing cellular fates

Abstract: Opposing cellular responses are typically regulated by distinct sets of genes. However, tissue transglutaminase (TGase) provides an interesting example of a single gene product that has been implicated both in affording protection against cellular insults as well as in promoting cell death. Here, we shed some light on how these conflicting activities might be manifested by demonstrating that alternative transcripts of TGase differentially affect cell viability. We show that although the full-length TGase prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 32 publications
(51 reference statements)
1
111
0
Order By: Relevance
“…Transglutaminase 2 has been implicated to be a participant in apoptotic process (Antonyak et al, 2006;Yamaguchi and Wang, 2006;Verma and Mehta, 2007 (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transglutaminase 2 has been implicated to be a participant in apoptotic process (Antonyak et al, 2006;Yamaguchi and Wang, 2006;Verma and Mehta, 2007 (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that NF-kB signal pathway is activated by hypoxic stress (Antonyak et al, 2006), and TG2 is involved in the activation of NF-kB signaling (Park et al, 2006). We examined the activation of NFkB signal pathway using reporter constructs containing NF-kB responsible elements (3kB-Luc, and cellular inhibitor of apoptosis 2 luciferase (cIAP2-Luc)).…”
Section: Activation Of Nuclear Factor (Nf)-kb Pathway By Transglutamimentioning
confidence: 99%
“…Figure 2A shows the Coomassie blue-stained SDS gel profile for wild-type TGase-2 and some representative examples of the mutants used in this study. Unlike the case for the TGase-S protein (28), none of the TGase-2 point-mutants showed detectable aggregation during their purification (data not shown). We then examined their GTP-binding capability by using a spectroscopic assay that takes advantage of the fluorescence properties of the GTP-analog, BODIPY-FL GTPγS (BOD-GTPγS).…”
Section: Generation Of Gtp-binding-defective Mutants Of Human Tgase-2mentioning
confidence: 99%
“…Recently, we have found that one possible explanation for these apparent discrepancies may arise from the alternative processing of the TGase-2 transcript (28). In fact, an alternative TGase-2 transcript was shown to be expressed in cells upon their treatment with cytokines, and interestingly, was also detected in the brains of Alzheimer's patients (29)(30)(31).…”
mentioning
confidence: 99%
See 1 more Smart Citation